Indigitization - Bickel, Rachel; Dupont, Sarah (KULA)

(untitled) (University of Victoria Libraries, 2018)
Indigitization is a British Columbia-based collaborative initiative between Indigenous communities and organizations, the Irving K. Barber Learning Centre (IKBLC), the Museum of Anthropology (MOA), the UBC iSchool at the University of British Columbia (UBC), and the University of Northern British Columbia (UNBC) Archives and Special Collections, to facilitate capacity building in Indigenous information management. This project is committed to clarifying processes and identifying issues in the conservation, digitization, and management of Indigenous community knowledge. It does so by providing information resources through the Indigitization toolkit and by enabling community-led audio cassette digitization projects through grant funding and training. Indigitization seeks to grow and work with a network of practitioners to develop effective practices for the management of digital heritage that support the goals of individual communities.